TALENT MANAGEMENT STRATEGIES TO IMPROVE EMPLOYEE PERFORMANCE AT BARANTIN - Akhmad Alfaraby; Edi Sugiono; Lijan Poltak Sinambela (Bajang Institute, 2025)
The development of an organization is inseparable from the support of both internal and external stakeholders, with human resource management (HRM) playing a critical strategic role in achieving organizational objectives. In the modern competitive environment, Talent Management (TM) has emerged as a key HRM practice to attract, develop, retain, and position individuals with the right skills to drive organizational success. This study aims to examine the effect of Talent Management strategies on Employee Performance (EP) at the Indonesian Quarantine Agency (Barantin). Drawing on theories from Collings and Mellahi (2009) and other prior research, the study emphasizes the importance of aligning TM initiatives with institutional goals to enhance productivity and service quality. A quantitative research method was applied, with data collected through purposive sampling from 160 employees. The analysis used Structural Equation Modeling (SEM) via SmartPLS to test the measurement and structural models. The R² value for EP was 0.819, indicating that Talent Management explains 81.9% of the variance in Employee Performance, while the Q² value of 0.689 confirms strong predictive relevance. Hypothesis testing results show a path coefficient of 0.905, a t-statistic of 43.460, and a p-value of 0.000, indicating a very strong, positive, and statistically significant effect of Talent Management on Employee Performance. The discussion highlights that systematic talent acquisition, targeted training and development, performance-based appraisal systems, and structured career pathways substantially contribute to enhancing work quality and productivity at Barantin. The findings align with previous studies in both public and private sectors, confirming that well-implemented TM strategies improve engagement, retention, and organizational outcomes. The exceptionally high correlation found in this study suggests that Barantin’s TM practices are highly customized to its operational needs, enabling effective skill utilization and superior performance. These results underscore the strategic importance of TM in public sector institutions and provide practical insights for policymakers and HR practitioners aiming to strengthen workforce capabilities.